Community Participation in the Development of Budo Tourism Village, Northern Minahasa Regency - Jeane Mantiri,; Margareth Rantung,; Nancy Onibala,; Herke Memah, (Technium Social Sciences Journal, 2024)
Community participation is a pattern of tourism village development that supports and enables full involvement by the local community in the planning, implementation, and management of tourism businesses and all benefits obtained. The development of a tourism village based on community participation in Budo Village in its management still does not maximise the potential and attractiveness of tourism. Communities located in the development area should be encouraged to identify their own goals and direct tourism development to improve the fulfilment of local community needs. The purpose of the study was to determine the involvement of the community in the development of tourist villages from the form and level of community participation, and examine the development model of tourist villages based on community participation. The method used in this research is a mixed method between qualitative with descriptive analysis, and quantitative with simple linear regression analysis. Through this study, it is expected that the strategic role of each stakeholder can encourage the community to be actively involved in the development of tourism villages. This research focused on identifying the potential of tourism villages and local wisdom values of Budo tourism village, and analysing tourism development based on community participation that will be developed into a model of community-based tourism village to support Likupang Special Economic Zone. The results showed that the form of community participation in the development of Budo tourism village at the partnership stage, and the level of participation in the planning stage is high, the implementation stage, the stage of receiving benefits and evaluation is quite high.